GENDER EQUALITY THROUGH THE EYES OF YOUTH: MODERN PERSPECTIVES AND APPROACHES (Modern education and development, 2025)
This article explores the issue of gender equality from the perspective of youth. The study analyzes modern attitudes of young people toward gender roles, stereotypes, and equal opportunities. Based on surveys and analysis, it identifies a positive shift in youth perceptions regarding gender equality. The article also highlights the crucial role of education and media in overcoming gender-related barriers.